FORMATE-PYRUVATE EXCHANGE REACTION IN STREPTOCOCCUS FAECALIS I. : Factor Requirement for Intact Cells - Wood, N. P. (1964)
Wood, N. P. (A. & M. College of Texas, College Station), and D. J. O'Kane. Formate-pyruvate exchange reaction in Streptococcus faecalis. I. Factor requirement for whole cells. J. Bacteriol. 87:97–103. 1964.—A factor present in plant and animal sources was found necessary for the incorporation of formate-C(14) into pyruvate by Streptococcus faecalis 10Cl. Yeast extract produced a response linear in the range between 10 and 30 mg/ml of reaction mixture. Soy peptone, beef peptone, and Brain Heart Infusion replaced yeast extract, but various intermediates, cofactors, amino acids, purines, pyrimidines, and peptides did not stimulate the reaction. A lag occurred in the rate of formate incorporation that was not influenced by anaerobic conditions or growth of cells in a medium containing pyruvate and formate. Phosphate or maleate buffer permitted rapid exchange velocities but tris(hydroxymethyl)aminomethane or collidine buffer was inhibitory. Heating yeast extract at 121 C for 15 min in 3 n H(2)SO(4) produced 66% inactivation of the factor(s), whereas treatment with 3 n KOH produced 97% inactivation. The factor(s) was insoluble in butanol, benzene, ethyl acetate, or chloroform. The material adsorbed on Dowex-1 (OH(−)) and Amberlite IR-120 (H(+)) but not on Amberlite IR-4B (OH(−)). The active component(s) was highly polar, nonvolatile, dialyzable, and had amphoteric properties.